Gods and beasts : a novel - Mina, Denise (Mina, Denise. Alex Morrow novel., 2013)
"It's the week before Christmas when a lone robber bursts into a busy Glasgow post office carrying an AK-47. An elderly man suddenly hands his young grandson to a stranger and wordlessly helps the gunman fill bags with cash, then carries them to the door. He opens the door and bows his head; the robber fires off the AK-47, tearing the grandfather in two. DS Alex Morrow arrives on the scene and finds that the alarm system had been disabled before the robbery. Yet upon investigation, none of the employees can be linked to the gunman. And the grandfather-a life-long campaigner for social justice-is above reproach. As Morrow searches for the killer, she discovers a hidden, sinister political network. Soon it is chillingly clear: no corner of the city is safe, and her involvement will go deeper than she could ever have imagined"--